Commercial genetic testing for type 2 polysaccharide storage myopathy and myofibrillar myopathy does not correspond to a histopathological diagnosis. (29th October 2020) - Valberg, Stephanie J.; Finno, Carrie J.; Henry, Marisa L.; Schott, Melissa; Velez‐Irizarry, Deborah; Peng, Sichong; McKenzie, Erica C.; Petersen, Jessica L.
Abstract: Background: Commercial genetic tests for type 2 polysaccharide storage myopathy (PSSM2) and myofibrillar myopathy (MFM) have not been validated by peer‐review, and formal regulation of veterinary genetic testing is lacking. Objectives: To compare genotype and allele frequencies of commercial test variants (P variants) in MYOT (P2; rs1138656462), FLNC (P3a; rs1139799323), FLNC (P3b; rs1142918816) and MYOZ3 (P4; rs1142544043) between Warmblood (WB) and Arabian (AR) horses diagnosed with PSSM2/MFM by muscle histopathology, and phenotyped breed‐matched controls. To quantify variant frequency in public repositories of ancient and modern horse breeds. Study design: Cross sectional using archived clinical material and publicly available data. Methods: We studied 54 control‐WB, 68 PSSM2/MFM‐WB, 30 control‐AR, 30 PSSM2/MFM‐AR and 205 public genotypes. Variants were genotyped by pyrosequencing archived DNA. Genotype and allele frequency, and number of variant alleles or loci were compared within breed between controls, PSSM2/MFM combined and MFM or PSSM2 horses considered separately using additive/genotypic and dominant models (Fisher's exact tests). Variant frequencies in modern, early domestic and Przewalski horses were determined from a public data repository. Results: There was no significant association between any P locus and a histopathological diagnosis of PSSM2/MFM, and no difference between control and myopathic horses in total loci with alternative alleles, or total alternate alleles when PSSM2/MFM was considered combined or separately as PSSM2 or MFM. For all tests, sensitivity was <0.33. Allele frequencies in WB (controls/cases) were: 8%/15% (P2), 5%/6% (P3a/b) and 9%/13% (P4); in AR, frequencies were: 12%/17% (P2), 2%/2% (P3a/b) and 7%/12% (P4). All P variants were present in early domestic (400‐ to 5500‐year‐old) horses and P2 present in the Przewalski. Conclusions: Because of the lack of significant association between a histopathological diagnosis of PSSM2 or MFM and the commercial genetic test variants P2, P3 and P4 in WB and AR, we cannot recommend the use of these variant genotypes for selection and breeding, prepurchase examination or diagnosis of a myopathy.